ICS Teaching Module: Detrusor Leak Point Pressures in Patients With Relevant Neurological Abnormalities - TARCAN, TUFAN (WILEY, 2017)
Aims: This manuscript serves as a scientific background review; the evidence base, for the presentation made available on ICS website to summarize current knowledge and recommendations for the measurement and use of the DLPP. Methods: This review has been prepared by a Working Group of The ICS Urodynamics Committee. The methodology used included comprehensive literature review, consensus formation by the members of the Working Group, and review by members of the ICS Urodynamics Committee core panel. Results: DLPP has been recommended and utilized in the urodynamic evaluation of N-LUTD for many years, but it lacks standardization and there are numerous pitfalls in its measurement. EFP and LPP associated with N-DO are frequently and mistakenly reported as DLPP. The information that high DLPP predicts UUTD originates from retrospective cohort studies of a low level of evidence ( LoE 3). Existing data confirm that patients with lower DLPP do better than patients with higher DLPP in terms of their upper urinary tract. However, there appears to be no reliable 'safe/nosafe' cut-off for DLPP since there are other urodynamic factors that influence UUTD such as bladder compliance and more. Conclusion: Although higher DLPP is associated with a greater risk of UUTD, there is no reliable cut-off level to undoubtedly discriminate the risky group, including the traditional cutoff level of 40 cm H2O. Therefore, DLPP should not be used as the sole urodynamic parameter. Future research should be directed to standardization of the technique and better classification of DLPP cut-offs in N-LUTD. (C) 2015 Wiley Periodicals, Inc.
Keywords: detrusor leak point pressure; neurogenic bladder; urodynamics; URINARY-TRACT DETERIORATION; NEUROGENIC BLADDER; CONTINENCE-SOCIETY; CHILDREN; MYELODYSPLASIA; STANDARDIZATION; TERMINOLOGY; COMMITTEE